Tumor cell heterogeneity in Small Cell Lung Cancer (SCLC): phenotypical and functional differences associated with Epithelial-Mesenchymal Transition (EMT) and DNA methylation changes - Krohn, Alexander; Ahrens, Theresa; Yalcin, Arzu; Ploenes, Till; Wehrle, Julius; Taromi, Sanaz; Wollner, Stefan; Follo, Marie; Brabletz, Thomas; Mani, Sendurai A.; Claus, Rainer; Hackanson, Bjoern; et al. (PLoS ONE, 2014)
Small Cell Lung Cancer (SCLC) is a specific subtype of lung cancer presenting as highly metastatic disease with extremely poor prognosis. Despite responding initially well to chemo- or radiotherapy, SCLC almost invariably relapses and develops resistance to chemotherapy. This is suspected to be related to tumor cell subpopulations with different characteristics resembling stem cells. Epithelial-Mesenchymal Transition (EMT) is known to play a key role in metastatic processes and in developing drug resistance. This is also true for NSCLC, but there is very little information on EMT processes in SCLC so far. SCLC, in contrast to NSCLC cell lines, grow mainly in floating cell clusters and a minor part as adherent cells. We compared these morphologically different subpopulations of SCLC cell lines for EMT and epigenetic features, detecting significant differences in the adherent subpopulations with high levels of mesenchymal markers such as Vimentin and Fibronectin and very low levels of epithelial markers like E-cadherin and Zona Occludens 1. In addition, expression of EMT-related transcription factors such as Snail/Snai1, Slug/Snai2, and Zeb1, DNA methylation patterns of the EMT hallmark genes, functional responses like migration, invasion, matrix metalloproteases secretion, and resistance to chemotherapeutic drug treatment all differed significantly between the sublines. This phenotypic variability might reflect tumor cell heterogeneity and EMT during metastasis in vivo, accompanied by the development of refractory disease in relapse. We propose that epigenetic regulation plays a key role during phenotypical and functional changes in tumor cells and might therefore provide new treatment options for SCLC patients.
EVALuna2:10195